PENGEMBANGAN MEDIA KARTU DOMINO CUCI TANGAN PAKAI SABUN PADA SISWA - Setiawan, Ridwan; Rizkia, Sahren Amalia (Poltekkes Kemenkes Bengkulu, 2023)
Handwashing with soap (CTPS) is one of the efforts to prevent diseases, especially diarrhea. There’s a low number of students’ behavior of CTPS, so it is necessary to increase students' knowledge about CTPS with media learning in the form domino card. The purpose of this study is to develop CTPS domino card media with ADDIE approach model. This type of research uses R&D with the ADDIE approach model. The population of this study were all 4th grade students of SDN Resmitinggal with sampling using the total sampling technique. Data collection in this study by filling out a questionnaire which will be analyzed paired sample t-test. Results, The domino card media learning that are catching, easy to remember, and can be use to learn together with friends by considering the name, font, size, image and color of the card. The design of domino card is in the form of a logo with seven cards that symbolize the CTPS step, and its size is 6x10 cm. Media development is assessed by material experts with worthy criteria, and by media experts with very worthy criteria. Media implementation had been done with small-scale feasibility tests with very worthy category. Evaluation of CTPS domino card media shows that there is an influence of domino card media on CTPS knowledge in SDN students. So it can be concluded that CTPS domino card media is worth to use and there is an influence of domino card media on CTPS knowledge in SDN Resmitinggal students.